REPRESENTASI LGBT DALAM VIDEO KLIP “TOO GOOD AT GOODBYES” - Stara Asrita (Jurnal Komunikasi dan Kajian Media, 2020)
This study aims to find out the representation of LGBT in the video clip “Too Good at Goodbyes”. This qualitative study uses the semiotic analysis of John Fiske. The data analysis technique is The Codes of Television which are consist of three levels, namely the level of reality, the level of representation and the level of ideology. From the screenshot of the images in the video clip there are several results. First, the level of the reality, LGBT couples who are cast performers show sad expressions with soft gestures whent they hugging their homosexual partners. The conditions sorruound them are very dramatic and quiet. Then, the level of representation, the shooting method is done with close up and medium shots to get how the face of the cast before saying goodbyes from their partners. Third, at the level of ideology, there are LGBT discourse in the video clip. Sam Smith revealed through the lirics and the existing scenes that LGBT community also have a romantic problems like common peeople.